A comprehensive review on adsorptive removal of azo dyes using functional materials - Khan, Afsar; Ju, Peiwen; Han, Zhengwei; Ni, Chenquan (Aqua (London, England), 2024)
The shortage of freshwater resources caused by azo dye pollution is an acute global issue, which has a great impact on environmental protection and human health. Therefore, the use of new strategies for designing and synthesizing green, efficient, and economical materials for the removal of azo dyes is required. Among the various methods for removal of azo dyes, adsorption by using advanced functional materials, including nanomaterials, metal oxides, metal oxides–polymer composite, biomaterials, and porous materials, have attracted significant attention over the past few years because of their capabilities of brilliant removal efficiency, high selectivity, quick response, reversibility, flexibility in operation, and less harmful by-products. In this review, we report the adsorption of azo dyes and general design principles underlying the above-mentioned functional materials and, in particular, highlight the fundamental mechanisms and effect of various environmental conditions; also, current challenges and opportunities in this exciting field have been emphasized, including the fabrication, subsequent treatment, and potential future applications of such functional materials.